Active power regulation for large-scale wind farms through an efficient power plant model of electric vehicles. (1st January 2017) - Wang, Mingshen; Mu, Yunfei; Jia, Hongjie; Wu, Jianzhong; Yu, Xiaodan; Qi, Yan
Highlights: Considering the travelling behaviors, an efficient power plant model of EVs (E-EPP) is developed. The available capacity of the EV aggregation is obtained with the E-EPP model under three charging scenarios. A new active power regulation strategy through E-EPP is proposed for the power system with large-scale wind farms. With the regulation strategy, the E-EPP can effectively decrease the output variation of traditional generators. Abstract: Considering the travelling behaviours of electric vehicles (EVs), an efficient power plant model of EVs (E-EPP) is developed for the active power regulation of the power system with large-scale wind farms. Based on the EV data base provided by the EU MERGE project, a generic V2G model (GVGM) is established. The Monte Carlo Simulation (MCS) method is implemented within the E-EPP to obtain the available response capacity of the EVs. A new active power regulation strategy based on the E-EPP is developed. A modified IEEE 118-bus system integrated with large-scale wind farms is used to verify the E-EPP model with the active power regulation strategy under different charging scenarios (dumb charging, smart charging and hybrid charging). The simulation results show that the E-EPP can improve the operating security and stability of the power system. The operation cost and the carbon emission are decreased by introducing large-scale wind farms.